Meningkatkan Keterampilan Menulis Karangan Sederhana Menggunakan Model Concept Sentence Berbantuan Media Gambar Siswa Kelas IV SDN 107419 Serdang - Sintia Sianturi, Robinson Hutagaol, Jheni Yusuf Saragih, Maria Friska Nainggolan, (Education Achievement: Journal of Science and Research, 2023)
The purpose of this study is to improve students’ writing skills of simple essays through concept sentence model assisted by picture media of fourth grade students at SDN.107419 Serdang. This research was classroom action research (CAR) Kemmis and Mc.Tanggart type which conducted in two cycles and each cycle consists of four stages: planning, action, observation, and reflection. The subjects of this study were fourth grade students, totaling 25 students. The data collection techniques were tests and observation sheets. The results showed that in pre-cycle stage only 9 students (36%) completed the standard value with an average score 59.8. In cycle 1 the number of students who completed the standard value increased to 16 students (64%) with an average score 60.8 and in cycle 2, the number of students who completed increased to 21 students (84%) with an average score of 82.56. It can be concluded that concept sentence model assisted by picture media can improve students’ writing skills of simple essays through concept sentence model assisted by picture media of fourth grade students at SDN.107419 Serdang.